State Responsibility in Protecting Women from the Trap of Online Loans: A Legal Analysis of the Consumer Protection Law and the ITE Law - Neri Tarigan, Luri (Jurnal Multidisiplin Sahombu, 2025)
Women are one of the most vulnerable groups to become victims of illegal online loans. The study aims to analyze the state's responsibility in protecting women from the trap of illegal online loans, with a focus on the legal protection aspects regulated in the Consumer Protection Law and the Electronic Information and Transactions Law. The study also identifies the role of policies and regulators in creating a fair protection system, and provides recommendations for strengthening legal protection for women in the online lending sector. The research method uses a normative legal approach, by analyzing applicable laws and regulations and related literature that supports the analysis of women's protection. The results of the study show that although there are regulations governing consumer protection, implementation in the field is still weak, and many women are trapped in illegal online loans which are not only financially detrimental but also have psychological impacts. The state's responsibility in this case includes strengthening law enforcement against illegal online loans, increasing financial and digital literacy among women, and protecting personal data. The study suggests the importance of collaboration between the government, private sector, and society to create a safer and more equitable environment for women in dealing with illegal online loans. Research reveals the importance of strengthening the role of policy and regulators in realizing a more effective protection system, especially by implementing more targeted education and literacy programs.